Absorptive Capacity: A New Perspective on Learning and Innovation - Cohen, Wesley M.; Levinthal, Daniel A. (Administrative Science Quarterly, 1990)
Wesley M. Cohen, Daniel A. Levinthal, Absorptive Capacity: A New Perspective on Learning and Innovation, Administrative Science Quarterly, Vol. 35, No. 1, Special Issue: Technology, Organizations, and Innovation (Mar., 1990), pp. 128-152